2021
DOI: 10.1177/01171968211017416
|View full text |Cite
|
Sign up to set email alerts
|

The structure of unemployment risk perception among migrant workers in China: An exploratory mixed methods study

Abstract: China has 287 million migrant workers and identifying and preventing their unemployment risk holds theoretical and practical significance. This study collected data in 2019 to explore the structure of migrant workers’ perception of unemployment risk. In the first stage of this study, in-depth interviews and grounded theory analysis were conducted and an interpretation framework for migrant workers’ unemployment risk perception (URP) was developed. In the second stage, a URP scale for migrant workers was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…According to risk perception theory, risk perception consists of a person's concerns about a specific thing or event, and it often showcases an individual's beliefs, attitudes, judgments, and emotions about risk (Wildavsky & Dake 1990;Parkinson 1993). Existing unemployment risk perception theories continue the logic of detraditionalisation found in risk perception research, where social issues are introduced through a psychology theoretical framework and presented based on individual perception (Broom, Rennie, & Strazdins et al 2006;Zheng et al 2021). Of course, due to individual preferences and experiences, people have ranging risk attitudes and risk perceptions when faced with different risks (Slovic 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…According to risk perception theory, risk perception consists of a person's concerns about a specific thing or event, and it often showcases an individual's beliefs, attitudes, judgments, and emotions about risk (Wildavsky & Dake 1990;Parkinson 1993). Existing unemployment risk perception theories continue the logic of detraditionalisation found in risk perception research, where social issues are introduced through a psychology theoretical framework and presented based on individual perception (Broom, Rennie, & Strazdins et al 2006;Zheng et al 2021). Of course, due to individual preferences and experiences, people have ranging risk attitudes and risk perceptions when faced with different risks (Slovic 1987).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urban unemployment stemming from labour market competition among low-skilled, low-capital, new-generation migrant workers can be considered as both economic deprivation and deprivation of opportunity. From this logic, the unemployment risk perception of new-generation migrant workers is essentially a manifestation of their sense of the relative deprivation of urban resources (Zheng et al 2021). Stark et al (1988) believed that the relative deprivation of urban resources is more likely to prompt potential migrant populations to make migration decisions and, under pressure, opt to stay in the destination city.…”
Section: Perception Of Unemployment Risk and Citizenship Willingnessmentioning
confidence: 99%
See 2 more Smart Citations
“…Zheng et al believe that the study of unemployment risk from the perspective of subjective unemployment risk perception can better explore the problem of unemployment risk from an individual perspective, and through structured in-depth interviews and grounded theoretical analysis, an explanatory framework for migrant workers' unemployment risk perception is constructed [6]. It is found that the unemployment risk perception is composed of psychological, financial, relationship, citizenship and re-immigration.…”
Section: Foreign Literature Reviewmentioning
confidence: 99%